Mechanism behind the degradation of aqueous norbixin upon storage in light and dark environment. (25th April 2020) - Møller, Anders Hauer; Jahangiri, Amita; Danielsen, Marianne; Madsen, Bjoern; Joernsgaard, Bjarne; Vaerbak, Signe; Hammershøj, Marianne; Dalsgaard, Trine Kastrup
Highlights: Norbixin oxidation products are formed both upon light and dark storage. Light accelerates the oxidation of norbixin. Norbixin oxidation products containing up to 5 oxidations were detected. The norbixin oxidation is suggested to involve a peroxyl radical chain reaction. Abstract: Buffered aqueous solutions of norbixin were stored in light and dark, and analyzed using mass spectrometry. Compounds with both higher and lower masses than norbixin were detected, suggesting the formation of oxidation products and oxidative cleavage products of norbixin. The norbixin oxidation products included compounds containing several oxidations. The amounts of oxidation products of norbixin increased during storage in both light and dark, but in light, the development accelerated. Scavengers of superoxide radical anion (superoxide dismutase), hydrogen peroxide (catalase), hydroxyl radicals (mannitol) and singlet oxygen (sodium azide) and carbon-centered radicals (DMPO) were tested to determine if any of the reactive species were involved in the degradation of norbixin. Of these, only DMPO decreased the bleaching of norbixin indicating the involvement of carbon-centered radicals. Multiple oxidations of norbixin might be a result of a radical chain reaction involving peroxyl and carbon-centered radicals even though not detectable with electron spin resonance.